(untitled) - Smajlović, Ermina (Germany, 2015)
Numerous changes in marketing environment of banks have determined the need for creation and implementation of new strategies that would enable accomplishment of strong competitive advantages. With that, we cannot neglect the fact that all banks offer the same or the similar type of services, which makes the process of differentiating own offers in relation to the competitive one very hard. Therefore, banks should recognise other possibilities of adaption to dynamic changes in the modern marketing environment. Starting with the attitude that strategic planning is a necessary condition for achievement of strong competitive advantages we shed light on the process of strategic planning in banks with a special focus on creation and choice of marketing strategies.
Keywords: Tiếp thị ngân hàng,Bank marketing